A new species of Agistemus Summers (Acari: Stigmaeidae), and key to all known species from Peru - Escobar-Garcia, Hector Alonso [UNESP] (2023)
A new species of the family Stigmaeidae, the genus Agistemus group terminalis, namely: A. peruvianus n. sp., inhabiting foliage of a native forest tree called algarrobo, Neltuma piurensis (Fabaceae), from Piura, north-western Peru, is described and illustrated based on females, males, and deutonymphs. The mites were found during spring, summer, and autumn, but more frequently observed autumn (March to June). A key to the Peru species of the genus Agistemus is provided.